Enhancing the control efficiency of plant extracts against Spodoptera frugiperda (Lepidoptera: Noctuoidea) through mixture formula development - Tipsut, Nattarat; Kumrungsee , Nutchaya; Pimsawang, Lalita; Pluempanupat, Wanchai; Bullangpoti, Vasakorn (Agriculture and Natural Resources, 2025)
Importance of this work: The fall armyworm, Spodoptera frugiperda, is a major agricultural pest, requiring effective and sustainable control methods. This study enhances control efficiency by developing a plant extract mixture that significantly increases mortality while reducing the required dosage. Objectives: To assess the insecticidal potential of various plant crude extracts against S. frugiperda larvae for the future development of effective insecticide products. Materials and methods: The insecticidal potential was investigated of various crude extracts from Cyperus rotundus mixed with Piper retrofractum against S. frugiperda larvae. The acute effects were determined of binary mixtures of various compounds at concentrations equal to the doses required to kill 30%, 20% and 10% of the tested population after the specified test duration (24 hr or 48 hr). Results: The best formulation was the combination of P. retrofractum hexane crude extract (at a dose of 10.57 parts per million, ppm) and C. rotundus dichloromethane extract (at a dose of 2,504 ppm), which caused mortality rates of up to 98% compared with 20% when the individual extracts were used. Main finding: This mixture formulation allowed the use of smaller amounts of plant substances, resulting in lower production costs. This information should be useful for the future development of effective insecticide products.